PENGARUH KESEHATAN BANK TERHADAP PERTUMBUHAN LABA DENGAN MENGGUNAKAN RASIO KEUANGAN (Students' Journal of Accounting and Banking, 2013)
The economic crisis in the banking sector resulted in difficulties in a variety of sectors, it is necessary to repair the health of banks in order to restore public trust by using financial ratios. The aim of this study was to obtain empirical evidence about the health of banks to profit growth using CAMEL. Independent variable in this study is CAR, KAP, NPM, ROA, BOPO and LDR. Dependent variable used in this study is earnings growth. The sample in this study are listed banking companies in Indonesia Stock Exchange (BEI) in the period between 2008-2011. Data collected by purposive sampling method. Total 24 banking companies were taken as study’s sample. The method of analysis in this research used the classic assumption test, the test model (F-test and the coefficient of determination), multiple linear regression analysis, and t-test. The results of this research showed that simultaneously is known that CAR, KAP, NPM, ROA, BOPO and LDR significantly affected. Being of the partial test result that the value of the CAR, NPM, BOPO and LDR have positive and significant effect on profit growth. KAP variable is positive and unsignificant, while ROA variable is negative and unsignificant on growth earnings. Keywords: Earnings Growth, CAR, KAP, NPM, ROA, BOPO and LDR.